Design and experiment of ground jujube picker based on bionic mechanism - Wang, Weijun; Liu, Zefeng; Rusul, Eli; Chen, Bangbang; Song, Xiyan; Song, Dongya; Yang, Hang; Zhang, Peng; Wang, Chenghao (International Journal of Agricultural and Biological Engineering, 2025)
For mechanized picking of ground jujube under thick planting mode, there arise such issues as ease of damage and inefficient and difficult separation from impurities. In view of this, a bionic arm ground jujube picker was designed on the basis of analyzing jujube planting mode and characteristics, the structural parameters of its key components were determined, and a characteristic model for airflow in the internal flow field of the cleaning system and a movement trajectory model of the gathering device were established. A quadratic orthogonal center composite test was carried out to establish the regression models between influencing factors and the performance of the picker, and analyze the influence law of these factors on the picker. In this test, ground jujubes were taken as the picking object; the forward speed of the picker, the fan speed, and the height of the picking mouth from the ground were taken as the influencing factors; and the picking rate and the impurity rate were taken as the performance indices of the picker. The optimal combination of parameters was determined by multi-objective optimization (MOD): the forward speed of the picker was 0.47 m/s, the fan speed was 3025.76 r/min, and the height of the picking mouth from the ground was 84.20 mm. At this time, the picking rate of the picker was 94.00%, and the impurity rate was 2.30%. According to test verification, the test results and optimization results were consistent, meeting the requirements of mechanized picking of ground jujube. Key words: jujube picker; Fluent simulation; test design; cleaning systemDOI: 10.25165/j.ijabe.20251802.8915Citation: Wang W J, Liu Z F, Eli·rusul, Chen B B, Song X Y, Song D Y, et al. Design and experiment of ground jujube picker based on bionic mechanism. Int J Agric & Biol Eng, 2025; 18(2): 35–44.